Efficacy and Safety of Available Protocols for Aspirin Hypersensitivity for Patients Undergoing Percutaneous Coronary Intervention: A Survey and Systematic Review. (January 2016) - Bianco, Matteo; Bernardi, Alessandro; D'Ascenzo, Fabrizio; Cerrato, Enrico; Omedè, Pierluigi; Montefusco, Antonio; DiNicolantonio, James J.; Zoccai, Giuseppe Biondi; Varbella, Ferdinando; Carini, Giovanni; Moretti, Claudio; Pozzi, Roberto; et al.
Abstract : Background—: The most suitable approach for patients with aspirin hypersensitivity undergoing percutaneous coronary intervention remains to be assessed. Methods and Results—: Pubmed, Google Scholar, and Cochrane were systematically searched for papers describing protocols about aspirin hypersensitivity in the percutaneous coronary intervention setting. Discharge from hospital with aspirin was the primary end point, whereas rates of adverse reactions being a secondary outcome. An online international survey was performed to critically analyze rates of aspirin hypersensitivity and its medical and interventional management. Eleven studies with 283 patients were included. An endovenous desensitization protocol was performed on one of them, with high efficacy rate (98%) and a low adverse reaction rate when compared with oral administration. No significant differences were reported among the oral protocols in terms of efficacy (less versus more fractionated [95.8% {95.4%–96.2%} versus 95.9% {95.2–96.5%}]), whereas higher incidence of rash and angioedema were reported for protocols with <6 doses escalation (2.6% [1.1%–4.1%] versus 2.6% [1.9%–3.2%]). In the survey, we collected answer from 86 physician of the 100 interviewed. Fifty-six percent of them managed aspirin hypersensitivity changing the therapeutic regimen (eg, clopidogrel monotherapy and indobufen). Despite the previous safety data, desensitization protocols were adopted by only 42% of surveyed cardiologist. Conclusions—: Available protocols for aspirin hypersensitivity are effective and safe, representing a feasible approach for patients needing dual antiplatelet therapy. Abstract : Supplemental Digital Content is available in the text.